Pengaruh Proporsi Pinang dan Ekstrak Teh Hijau Terhadap Hasil Jadi Body Lotion - Adhitya Putri Sukmawati; Biyan Yesi Wilujeng; Octaverina Kecvara Pritasari; Fernanda, M.A. Hanny Ferry (Program Studi Pendidikan Tata Rias, 2025)
Exposure to UV rays in Indonesia causes skin damage such as premature aging. This research aims to develop a body lotion formulation combining areca nut extract and green tea leaf extract to protect and repair the skin, as well as for the the analysis the effect of the impact of the two extracts on organoleptic properties and determine the best formula based on the preference levels of the panelists. In this study, the method applied is a true experimental design involving 30 panelists from the Makeup Arts Department at State University of Surabaya. Three body lotion formulas were tested based on five organoleptic parameters: aroma, color, adhesion, homogeneity, and preference level. Data processing used one-way ANOVA and Duncan’s subsequent test. The study’s research findings show that the characteristics of color are significantly impacted, homogeneity, and level of preference (p < 0.05), whereas the aroma and adhesion values obtained exceeded the significance threshold, hence the differences are considered not significant (p > 0.05). Formula X3 (0.5 g of areca nut extract and 2 g of green tea extract) is the best formula because it received the highest score in almost all tested parameters.